A novel nutritional index as a predictor of mortality in dilated cardiomyopathy: a retrospective study - Can Wang; Yali Qing; Wuxian Chen; Gaoye Li (PeerJ, 2022)
Background Research has associated nutritional status with the prognosis of cardiovascular diseases. This study aimed to investigate the prognostic value of a novel nutritional index, triglycerides × total cholesterol × body weight index (TCBI), in patients with dilated cardiomyopathy (DCM). Methods This retrospective cohort study enrolled 445 patients with DCM. The median follow-up period was 2.8 years, and the primary endpoint was all-cause death. Results During follow-up, the all-cause mortality was observed in 135 out of 445 patients (30.3%). In Kaplan–Meier survival analysis, the third TCBI tertile had a lower mortality risk (T3 vs. T2 vs. T1: 16.9% vs. 35.1% vs. 38.9%; log-rank P < 0.001). In the multivariable Cox regression analysis, patients in the third tertile were associated with a decreased mortality, whereas there was no significant difference between the T2 and T1 groups. Moreover, TCBI could significantly improve risk stratification (continuous net reclassification improvement and integrated discrimination improvement) over the Geriatric Nutritional Risk Index (GNRI) and N-terminal pro-brain natriuretic peptide (NT-proBNP). Conclusions TCBI is independently associated with long-term survival in patients with DCM. Combination of TCBI and other biomarkers, such as GNRI and NT-proBNP, can significantly improve prognostic prediction. Further studies with larger sample size are required to validate our results.